Analyzing Consumer Preferences For Mie Gacoan Product Attributes Through Conjoint Analysis In Surabaya - Grecia Pratidina; Jariyah Jariah; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aimed to analyze consumer preferences toward Mie Gacoan product attributes in Surabaya using conjoint analysis. The research employed a survey method with 100 respondents selected through non-probability sampling. The attributes examined included noodle variants, menu completeness, payment method, and ordering type. The results showed that noodle variant was the most important attribute (42.42%), followed by menu completeness (28.15%), ordering type (17.83%), and payment method (11.60%). The highest utility values were found for Mie Gacoan's sweet-spicy flavour, the complete bundling package, dine-in service, and the cashless payment method. These findings indicate that product variety and service convenience significantly influence consumer purchasing decisions. The model demonstrated good predictive accuracy (p = 0.000), confirming the reliability of conjoint analysis in explaining consumer preferences. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals